2012
DOI: 10.1590/s0080-62342012000300021
|View full text |Cite
|
Sign up to set email alerts
|

Vivência do sofrimento moral na enfermagem: percepção da enfermeira

Abstract: Objetivando conhecer a percepção do sofrimento moral vivenciado, relacionando frequência e intensidade, realizou-se pesquisa Survey, utilizando escala Likert variando de 0 a 6 pontos, com 124 enfermeiras em hospitais do sul do Brasil, no ano de 2008. Mediante questionário autoaplicável e análise fatorial, foram identificados e validados quatro constructos. Os resultados finais foram obtidos através de três diferentes análises: 1) estatística descritiva; 2) análises de variância 3) regressão múltipla. O constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
18

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 11 publications
1
32
1
18
Order By: Relevance
“…Differently from a study carried out previously with Brazilian nurses (2) in which 70.2% of the nurses stated that they held team meetings, it was noted that meetings were held infrequently; nevertheless, comparing information (about holding meetings) with data related to the perception of MD -distinct in the two hospitals -it was ascertained that they had a significant relationship.…”
Section: It Was Verified That Workers Who Work In Uhsmentioning
confidence: 72%
See 4 more Smart Citations
“…Differently from a study carried out previously with Brazilian nurses (2) in which 70.2% of the nurses stated that they held team meetings, it was noted that meetings were held infrequently; nevertheless, comparing information (about holding meetings) with data related to the perception of MD -distinct in the two hospitals -it was ascertained that they had a significant relationship.…”
Section: It Was Verified That Workers Who Work In Uhsmentioning
confidence: 72%
“…In this study, the authors observed significant differences (at a level of 5%) in the It was also determined that only 29.5% of the nursing technicians and auxiliary nurses invested in their professional training after the end of their initial training course. Thus, the perception of problems in the area of health and nursing in its moral aspect seems to be benefitted when professional qualification and competence are higher (2) . One strategy identified for nursing professionals to understand both the importance of acting collectively and how much their professional knowledge could alter the reality is education in nursing (24) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations